MENTORING MANAGEMENT, PRODUCTIVE FINANCING, AND SHARIA FINANCIAL INCLUSION AS DETERMINANTS OF THE WELFARE OF HALAL MSMES IN LHOKSEUMAWE CITY - Muhammad Hafizh; Mutia Rahmah; Muttaqien (RADJA PUBLIKA, 2025)
This study aims to examine the influence of mentoring management, productive financing, and Islamic financial inclusion on the welfare of sustainable halal MSMEs in Lhokseumawe City. The research approach uses a descriptive quantitative method, where primary data is collected through distributing questionnaires to halal MSMEs selected using a purposive sampling technique. Descriptive data analysis methods are carried out using multiple linear regression to determine the partial and overall effects between variables and their relationships. The findings of this study are expected to show that effective management mentoring, easy access to productive financing, as well as financial inclusion and participation in Islamic finance contribute positively to improving the welfare of halal MSMEs in Lhokseumawe City. The original value of this study lies in the analysis of the integration of three key factors of Islamic economic empowerment in one empirical model that has not been widely carried out in local contexts such as Lhokseumawe. In addition, the results of this study provide practical implications for strengthening regional policies, Islamic financial institutions, and mentoring institutions in designing appropriate and value-based interventions to support the sustainability of halal MSMEs. The results of the study indicate that partially, the variables of productive financing and Islamic financial inclusion significantly influence the welfare of halal MSMEs in Lhokseumawe City, while mentoring management does not show a significant effect, although the direction of the influence is positive. However, simultaneously, the third variable significantly influences the welfare of halal MSMEs, with a contribution of 64.1% (Adjusted R² = 0.641). This study offers theoretical and practical contributions by integrating three elements of Islamic economic empowerment within a comprehensive conceptual framework. These findings reinforce the importance of a holistic, sharia-based approach in efforts to improve the economic welfare of marginalized communities. The implications of this study encourage Islamic financial institutions to not only focus on the financing aspect, but also strengthen their educational and social functions through mentoring and improving financial literacy.